Strategi Kreatif Penggunaan Visual Perempuan pada Kemasan Liquid Vape Katanya - Randy Desiawan; Agustrijanto (UNIVERSITAS KALBIS, 2022)
The media for implementing creative strategies are very diverse, including through packaging. Packaging can not only protect products, but can also be a means of communicating their products. The use of pictures of women on the packaging is a creative strategy of Liquid Vape Katanya. On the packaging, the pictures of women show an expression of a smile, with their hands shut. Researchers see that Triangle Brew, as a producer of liquid, has something to communicate. The aim of this study is therefore to determine the creative strategies for using images of women in their Liquid Vape Katanya. This research method is qualitative in that data is collected through interviews. The results of this study are the visuals of women as the identity and life of products, the visual expression of women is a form of admiration, the last one is to arouse interest, especially in male consumers.